The nuclear activity of the actin‐binding Moesin protein is necessary for gene expression in Drosophila. (5th March 2021) - Bajusz, Csaba; Kristó, Ildikó; Abonyi, Csilla; Venit, Tomáš; Vedelek, Viktor; Lukácsovich, Tamás; Farkas, Attila; Borkúti, Péter; Kovács, Zoltán; Bajusz, Izabella; Marton, Annamária; Vizler, Csaba; et al.
Abstract : Ezrin–Radixin–Moesin (ERM) proteins play an essential role in the cytoplasm by cross‐linking actin filaments with plasma membrane proteins. Research has identified the nuclear localization of ERMs, as well as the involvement of a single Drosophila ERM protein, Moesin, in nuclear mRNA exports. However, the question of how important the nuclear activity of ERM proteins are for the life of an organism has so far not been explored. Here, we present the first attempt to reveal the in vivo relevance of nuclear localization of Moesin in Drosophila . With the help of a nuclear export signal, we decreased the amount of Moesin in the nuclei of the animals. Furthermore, we observed various developmental defects, demonstrating the importance of ERM function in the nucleus for the first time. Transcriptome analysis of the mutant flies revealed that the lack of nuclear Moesin function leads to expression changes in nearly 700 genes, among them heat‐shock genes. This result together with additional findings revealed that in Drosophila the expression of protein chaperones requires the nuclear functions of Moesin. Database: GEO accession number: GSE155778 . Abstract : The dynamics and cross‐linking of the actin cytoskeleton with the plasma membrane are mediated by cytoplasmic Ezrin–Radixin–Moesin (ERM) proteins. However, nuclear roles for ERM have been described: the Drosophila ERM Moesin participates in mRNA export. Now, Péter Vilmos and colleagues addressed this nuclear role in situ through the creation of flies with only cytoplasmic Moesin. They observe numerous defects in the absence of nuclear Moesin, from embryonic lethality to developmental malformations. Importantly, Moesin is involved in the transcription of several hundred genes, including heat‐shock genes. This work provides in vivo evidence on the relevance of nuclear ERM proteins.